Pengaruh Model Problem Based Learning Terintegrasi Green Chemistry Terhadap Kemampuan Berpikir Kritis Siswa Kelas XI MIPA SMA Negeri 2 Narmada - Siti Sundari; Yunita Arian Sani Anwar; Muntari Muntari (FKIP University of Mataram, 2026)
This study aims to determine the effect of implementing of the problem-based learning model integrated with green chemistry on the critical thinking skills of grade XI MIPA students of SMA Negeri 2 Narmada. The research method used was a quasi-experimental design with a non-equivalent pretest posttest control group design. The population of this study was all grade XI MIPA students of SMA Negeri 2 Narmada, totaling 3 classes. The sampling technique used a random sampling technique, obtained Class XI MIPA 3 students as the experimental class and Class XI MIPA 1 students as the control class. The research instrument was a critical thinking ability test based on critical thinking indicators according to Ennis. Data analysis used the N-gain calculation, obtained a average N-gain value of the experimental class of 0.587 with a medium category and the control class of 0.382 with a medium category. The hypothesis was tested using the t-test, obtained the value of t count = 3.416 and t table = 1.681 at a significance level of 5% so that t count > t table. Thus, Ha was accepted, meaning that there was a positive influence from the application of the integrated green chemistry problem based learning (PBL) model on students' critical thinking abilities.